IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH NOMOR 2 TAHUN 2013 TERHADAP PENANGGULANGAN HIV DAN AIDS DI KABUPATEN SIDENRENG RAPPANG PROVINSI SULAWESI SELATAN - Herman D Herman D; Ahmad Yasin; Indra Anugrah (AkMen JURNAL ILMIAH, 2017)
Kebijakan HIV and AIDS in Sidenreng Rappang the government's efforts to address HIV and AIDS, but the implementation of the policy can not suppress the spread of the disease. Efforts are being made consisting of prevention, treatment, and rehabilitation. This study aimed to describe the process of implementation of the HIV and AIDS policy that has been done by the government Sidenreng Rappang and to illustrate the effect of policy implementation against HIV and AIDS. This research uses descriptive quantitative method. The sampling technique is purposive sampling. Data collection methods used through observation, questionnaires (questionnaire) and technical literature. The data analysis technique that collected data is simple regression analysis with SPSS 21 for windows. The results of the analysis in the form of descriptive statistics, test data quality, classic assumption test, simple regression analysis and hypothesis testing. The results showed that, on a variable policy implementation in each indicator to get a percentage, ie, indicator policy provisions of 31.2%, an indicator of the implementing provisions are in percentages of 29.8%, an indicator of the target provisions that are in a percentage of 35.8 % and an indicator environment provisions that are in percentages of 31.5%, an indicator of the provisions in the category once or percentage of 38.2%. In the variable response to HIV and AIDS prevention efforts in the category ever with a percentage of 39%, the handling in the category ever with a percentage of 28.4% and rehabilitation efforts in the category ever with a percentage of 25.6%. Implementation of Government policy affects the response to HIV and AIDS in Sidenreng Rappang, 50.2% to be in good enough category.